EDUCAÇÃO FÍSICA ESCOLAR: PERSPECTIVAS E CONCRETITUDES NO INTERIOR DO NORDESTE - da Silva Araujo, Regina; Robson Carvalho Lima, Gieudo; Cesar da Silva Oliveira, Edvaldo (Revista Form@re - Parfor/UFPI, 2026)
.